Ruling Russia : politics and administration in the Age of Absolutism, 1762-1796 - LeDonne, John P., 1935- (Studies of the Harriman Institute., 1984)
This book explores thoroughly the reforms of Russian administration from 1775 to 1785, this work also reaches beyond Catherine's reign to challenge established opinions on the nature of eighteenth-century Russian government and the autocracy of the tsars. Originally published in 1984. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.